Wabah dan Fenomena Covid-19 dalam Pandangan Ibn Sina - Mujtaba, Wardah (Jurnal Riset Agama, 2023)
This research aims to discuss Ibn Sina's thoughts related to the plague and the Covid-19 phenomenon. This research is very important to discuss because Ibn Sina is one of the muslim philosophers who has a link to how to deal with the Covid-19 phenomenon. This research uses a qualitative literature study method. As for the results and discussion in this study, Ibn Sina is one of the leading muslim philosophers and scientists who can be used as a benchmark for society in dealing with the plague. In this case that Ibn Sina's view, regarding the plague that can be faced by always maintaining health. This corona virus is a form of learning for the community, especially the muslim community to always get closer to Allah Swt. as said by Ibn Sina that every phenomenon that occurs must have wisdom. Therefore, there is a link between Ibn Sina's Thought and the Covid-19 phenomenon and synergizing with historical facts taught in Islam to address problems that occur in modern society can be addressed more wisely in facing challenges in the midst of the Covid-19 phenomenon and being able to strengthen ukhuwah fellow muslims. This research is an important thing in showing that the Covid-19 pandemic has a major influence on the social conditions of society.